Synthesis, dyeing performance and surface finishing effects of aminoethyl methacrylate functionalized stilbene fluorescent whitening agents - Meng Ou; Li Hua; Mao-sheng Wan; Bo Wang; Fei-qing Rao (Scientific Reports)
Abstract Six novel stilbene fluorescent whitening agents bearing aminoethyl methacrylate groups were synthesized. Their molecular orbital energy levels, thermal stability, dyeing performance, and surface-finishing efficacy on cotton fibers were systematically characterized. The resulting compounds 6a-f exhibited high thermal decomposition temperatures and low orbital energy differences, contributing to exceptional whitening and surface finishing effects on pure cotton. Treated fibers achieved a whiteness value of 127.49—a 50.81 unit increase over untreated cotton. The yellow/blue index decreased by 10.82, confirming significant whitening and color enhancement. Moreover, fiber surfaces displayed improved smoothness, indicating effective finishing. Among these, Compound 6a demonstrated optimal performance and emerges as a promising multifunctional material for simultaneous high efficiency whitening and surface finishing.